Submucosal fibrosis in large colorectal serrated lesions in cases receiving endoscopic submucosal dissection - Erik Manriquez-Alegria; Naohisa Yoshida; Reo Kobayashi; Naoto Iwai; Ken Inoue; Osamu Dohi; Lucas Cardoso; Hideyuki Konishi (Therapeutic Advances in Gastroenterology)
Background: Submucosal fibrosis is a known risk factor for adverse outcomes in colorectal endoscopic submucosal dissection (ESD). However, evidence regarding the presence and impact of fibrosis in colorectal serrated lesions (CSLs) remains limited. Objectives: This study aimed to evaluate the association between CSLs and submucosal fibrosis, and to assess the impact of fibrosis presence on therapeutic outcomes of colorectal ESD. Design: Retrospective cohort study. Methods: We retrospectively reviewed consecutive colorectal ESD cases performed between 2020 and 2024. Only lesions ⩾20 mm were included; cases were classified as CSLs and adenoma + T1 cancer according to histological diagnosis. CSLs included sessile serrated lesions (SSL), traditional serrated adenomas, SSL with dysplasia, and unclassified serrated adenomas. Patient/lesion characteristics, presence of fibrosis, severe fibrosis, and ESD outcomes were assessed. Multivariate analyses, including CSLs’ histology, were performed to identify factors associated with the presence of submucosal fibrosis and severe fibrosis. Results: A total of 445 colorectal ESD cases were included, comprising 72 CSLs and 373 adenoma + T1 cancer. CSLs were significantly associated with a lower presence of fibrosis (34.7% and 48.5%, p  = 0.04) and severe fibrosis (6.9% vs 18.2%; p  = 0.03) compared to adenoma + T1 cancer. In multivariate analysis, CSLs’ histology (odds ratio (OR): 0.58; p  = 0.04), lesion size ⩾40 mm (OR: 2.03; p  < 0.01), and rectal location (OR: 0.40; p  < 0.01) were significantly related to fibrosis presence. Lesion size ⩾40 mm (OR: 2.45; p  < 0.01) and polypoid morphology (OR: 3.42; p  < 0.01) were significantly related to severe fibrosis. Conclusion: CSLs’ histology was negatively correlated with submucosal fibrosis in colorectal ESD.